Lenvatinib-induced pemphigus erythematosus in hepatocellular carcinoma: a unique case report - Li, Xiaoqing; Ma, Suhua; She, Qing; Liu, Zirong; Liu, Yanan; Kuang, Yanjing; Huang, Xiaozhun; Zhan, Zhengyin (Frontiers in Oncology, 2025)
Adjuvant lenvatinib in combination with transarterial chemoembolization (TACE) has demonstrated prolonged disease-free survival in hepatocellular carcinoma patients at high risk of recurrence post-resection. Here, we present the case of a 68-year-old woman who developed serious side effects including pemphigus erythematosus (PE) linked to lenvatinib usage. Initially treated for breast cancer with radical surgery in April 2018 followed by adjuvant therapy, she was later diagnosed with liver cancer, initially mistaken for metastatic breast cancer to the liver. Although systemic treatment for advanced breast cancer was received, the tumor continued to progress and required partial removal of the liver after final evaluation. Subsequent pathology revealed hepatocellular carcinoma combined with risk factors for recurrence, prompting adjuvant therapy with TACE and oral lenvatinib. After three weeks of lenvatinib administration, the patient developed a skin rash diagnosed as PE through skin pathology. Treatment involved oral methylprednisolone, intravenous human immune globulin, and supportive care, resulting in a cure within a month. This unique case highlights the importance of further research not only on lenvatinib but also on monitoring and managing adverse reactions associated with targeted drugs to optimize patient safety and treatment outcomes.